Smart System Design For Toyota Kijang Super Electrical Cars Based on Microcontroller - Gunandar A; Martinus Martinus (International Conference on Engineering and Technology Development (ICETD), 2017)
Electrical system body has a role important in a vehicle that is as the main lighting when traveling at night as well as cues to signal to other drivers when turning and braking and honking horns as one element of safety in a vehicle as a whole. Lighting systems (lighting system) divided into 2 of the lighting system inside and outside lighting system. A microcontroller is a microprocessor that is devoted to instrumentation and control. Microprocessor is a digital electronic device that has inputs and outputs as well as control with a program that can be written and erased in a special way. Microcontroller is a chip in the form of IC (Integrated Circuit) that can receive input signals, process them and provide an output signal in accordance with a program that is loaded into it ". Microcontroller input signal coming from the sensor that is information from the environment while the output signal addressed to the actuator to give effect to the environment. arduino is an electronic kit or open source electronic circuit board in which there is a major component, ie a chip AVR microcontroller with the type of company Atmel.Tujuan of this design can be used as a medium of learning in SMK Negeri 1 KETAPANG LAMPUNG SOUTH particular subjects electrical system Toyota kijang car vehicle body super. The design was carried out from April to the month of July 2017 at the Workshop School SMK Negeri 1 KETAPANG, located in the village Berundung, Parit 8, District of Ketapang, SOUTH LAMPUNG district.